Phylogenetic analysis and genetic diversity of Colletotrichum falcatum isolates causing sugarcane red rot disease in Bangladesh - Hossain, Md Imam; Ahmad, Khairulmazmi; Vadamalai, Ganesan; Siddiqui, Yasmeen; Saad, Norsazilawati; Ahmed, Osumanu Haruna; Mohd Hata, Erneeza; Adzmi, Fariz; Rashed, Osamah; Rahman, Muhammad Ziaur; Kutawa, Abdulaziz Bashir (MDPI AG, 2021)
Colletotrichum falcatum Went causes red rot disease in sugarcane farming in the tropical and sub-tropical regions. This disease causes significant economic loss to the sugarcane production industry. Successful disease management strategies depend on understanding the evolutionary relationship between pathogens, genetic diversity, and population structure, particularly at the intra-specific level. Forty-one isolates of C. falcatum were collected from different sugarcane farms across Bangladesh for molecular identification, phylogeny and genetic diversity study. The four genes namely, ITS-rDNA, β-tubulin, Actin and GAPDH sequences were conducted. All the 41 C. falcatum isolates showed a 99–100% similarity index to the conserved gene sequences in the GenBank database. The phylogram of the four genes revealed that C. falcatum isolates of Bangladesh clustered in the same clade and no distinct geographical structuring were evident within the clade. The four gene sequences revealed that C. falcatum isolates from Bangladesh differed from other countries´ isolates because of nucleotides substitution at different loci. The genetic structure of C. falcatum isolates were determined using ISSR marker generated 404 polymorphic loci from 10 selected markers. The percentage of polymorphic loci was 99.01. The genetic variability at species level was slightly higher than at population level. Total mean gene diversity at the species level was 0.1732 whereas at population level it was 0.1521. The cluster analysis divided 41 isolates into four main genetic groups and the principal component analysis was consistent with cluster analysis. To the best of our knowledge, this is the first finding on characterizing C. falcatum isolates infesting sugarcane in Bangladesh. The results of this present study provide important baseline information vis a vis C. falcatum phylogeny analysis and genetic diversity study.